Analisis Optimalisasi Persediaan Berdasarkan Metode Economic Order Quantity Pada UMKM Roti Bakar Adakah - Yulia, Yulia Prihatini; Romansyah, Romansyah Sahabuddin; Aulya, Aulya Dwi Maharani; Afifah, A. Afifah Humairah; Anira, Nur Anira Sila (Sekolah Tinggi Ilmu Ekonomi Surakarta, 2023)
This study aims to forecast sales and calculate the most economical amount of raw materials from UMKM Roti Bakar Adakah, with its best seller menu, namely Roti Bakar Choco Crunchy. In addition, this study also aims to determine the comparison of inventory control using the Economic Order Quantity (EOQ) method and according to the policies of UMKM Roti Bakar Adakah. This research is quantitative research with a descriptive approach. The data used is primary data, with data collection methods through interviews. The data that has been obtained is analyzed using the least square method and the EOQ method. The results showed that the sales prediction for the choco crunchy variant of toast in 2024 was 13,850 units. As for the most economical ordering of raw materials according to the EOQ method, for each order, namely the raw material for bread at 186 kg, jam at 85 kg, SKM at 67 kg, and margarine at 100 kg. With the frequency of orders in a year, namely on bread 15 times, jam 10 times, SKM 5 times, and margarine 7 times. When compared to the company's policy analysis, which is 52 times.